KRONIK FILMEDIA’S RECEPTION TOWARDS FLORIAN GALLENBERGER’S COLONIA - Hanifi, Muhammad Luthfan; Noor, Redyanto (Faculty of Humanities, Diponegoro University, 2020)
This paper analyzes the audience’s reception of Colonia, a 2016 film by Florian Gallenberger. As a popular work, Colonia is a docudrama film that presents historical events happened in Chile during the coup of General Augusto Pinochet in 1973. The problems analyzed in this article are the reception process of respondents and the quality of Colonia as popular films. The film is chosen for the study as it received five nominations from German Film Awards 2016 and won Bavarian Film Awards 2016 for Best Production category, but it only has a rating of 26% from 47 reviews by Rotten Tomatoes. The respondents involved in this study are members of Kronik Filmedia of Diponegoro University. Kronik Filmedia is the university film club that focuses on producing short films and appreciating films by conducting film discussions. The purpose of the study is to describe the reception processes of respondents who are affected by their horizon of expectations and to prove that not all of popular works are low literature. The theory used in this paper is the Aesthetic of Reception theory by Hans Robert Jauss. The main concept of this theory is horizon of expectations. Horizon of expectations is a reader’s preferences from the previous experiences or readings. For the methodology, this paper uses qualitative research and focus group discussion as the data collecting method. Focus group discussion is a gathering data method by means of interviewing respondents in a forum consisted of five to eight people. Focus group discussion is an effective method to observe a social phenomenon or a case study. The data obtained is then analyzed as texts to draw a conclusion. The research involves eight members of Kronik Filmedia as respondents. The results of the research show the reception of Kronik Filmedia as Colonia can satisfy and even surpass seven out of eight respondents’ horizon of expectations as the film goes to be more ‘interesting’ and ‘thrilling’. All respondents also view that Colonia is worth to be studied and discussed as those of high literature.